The Arp2/3 Inhibitory Protein Arpin Is Required for Intestinal Epithelial Barrier Integrity - Chánez-Paredes, Sandra; Montoya-García, Armando; Castro-Ochoa, Karla F.; García-Cordero, Julio; Cedillo-Barrón, Leticia; Shibayama, Mineko; Nava, Porfirio; Flemming, Sven; Schlegel, Nicolas; Gautreau, Alexis M.; Vargas-Robles, Hilda; Mondragón-Flores, Ricardo; et al. (Frontiers in Cell and Developmental Biology, 2021)
The intestinal epithelial barrier (IEB) depends on stable interepithelial protein complexes such as tight junctions (TJ), adherens junctions (AJ) and the actin cytoskeleton. During inflammation, the IEB is compromised due to TJ protein internalization and actin remodeling. An important actin regulator is the Arp2/3 complex, which induces actin branching. Activation of Arp2/3 by nucleation-promoting factors is required for the formation of epithelial monolayers, but little is known about the relevance of Arp2/3 inhibition and endogenous Arp2/3 inhibitory proteins for IEB regulation. We found that the recently identified Arp2/3 inhibitory protein arpin was strongly expressed in intestinal epithelial cells. Arpin expression decreased in response to TNFα and IFNγ treatment, whereas expression of gadkin and Pick1, other Arp2/3 inhibitors, remained unchanged. Of note, arpin co-precipitated with the TJ proteins occludin and claudin-1, and the AJ protein E-cadherin. Arpin depletion altered the architecture of both AJ and TJ, increased actin filament content and actomyosin contractility; and significantly increased epithelial permeability demonstrating that arpin is indeed required for maintaining IEB integrity. During experimental colitis in mice, arpin expression was also decreased. Analyzing colon tissues from ulcerative colitis patients by Western blot, we found different arpin levels with overall no significant changes. However, in acutely inflamed areas arpin was significantly reduced compared to non-inflamed areas. Importantly, patients receiving mesalazine had significantly higher arpin levels than untreated patients. As arpin depletion (theoretically meaning more active Arp2/3) increased permeability, we wanted to know whether Arp2/3 inhibition would show the opposite. Indeed, the specific Arp2/3 inhibitor CK666 ameliorated TNFα/IFNγ-induced permeability in established Caco-2 monolayers by preventing TJ disruption. CK666 treatment also attenuated colitis development, colon tissue damage, TJ disruption and permeability in DSS-treated mice. Our results demonstrate that loss of arpin triggers IEB dysfunction during inflammation; and that low arpin levels can be considered a novel hallmark of acute inflammation.